Coil Embolization for Coronary Artery Perforation: A Retrospective Analysis of 110 Patients. (12th November 2021) - Hachinohe, Daisuke; Kashima, Yoshifumi; Okada, Yuito; Kanno, Daitaro; Kobayashi, Ken; Kaneko, Umihiko; Sugie, Takuro; Tadano, Yutaka; Watanabe, Tomohiko; Shitan, Hidemasa; Haraguchi, Takuya; Morita, Yusuke; et al.
Abstract : Objective . Coil embolization (CE) for coronary artery perforation (CAP) has not been thoroughly evaluated. This study aimed to evaluate the extent of myocardial damage and impact on cardiac function after CE for CAP. Methods . A total of 110 consecutive patients treated with CE for CAP were retrospectively identified. The degree of myocardial damage and impact on cardiac function were evaluated. Results . Forty-nine (44.5%) cases involved chronic total occlusions. A guidewire was the cause of perforation in 97 (88.2%) patients. The success rate of CE was 98.2%. Almost all patients were prescribed either antiplatelet drugs or anticoagulant medication or both. Patients with perforation types III and IV were found to be prone to creatinine kinase (CK) elevation and epicardial main vessel perforation, thereby causing myocardial damage. No changes were noted in the ejection fraction (EF) in patients with type V distal perforation and collateral channel perforation, while patients with perforation of the epicardial main vessel may show impaired cardiac function afterward. Conclusions . CE is safe and effective for treating CAP, especially when collateral channels and distal vessels are involved. Meanwhile, efforts should be taken to prevent CAP in epicardial main vessels since it may be difficult to treat with CS and cause myocardial damage when bailed out with CE leading to vessel sacrifice. We found that it was not necessary to change the anticoagulant regimen after CE owing to its ability to achieve robust hemostasis.